Patterns of care-seeking for postpartum symptoms in urban Karachi, Pakistan: implications for intervention design - Hirani, Farzeen; Ariff, Shabina; Nathwani, Apsara Ali; Peerwani, Ghazal; Kalbarczyk, Anna; Sultana, Shazia; Kazi, Abdul Momin; Yousuf, Farheen; Lefevre, Amnesty E.; Bhutta, Shereen; Winch, Peter J.; Soofi, Sajid; et al. (Reproductive health, 2025)
Background In Pakistan, the maternal mortality rate is 186/100,000 live births, with postpartum (PP) or maternal sepsis being the third leading cause of maternal deaths. Delays in early identification and timely management of PP sepsis are associated with mortality and severe maternal outcomes, including septicemia, neonatal deaths, infertility, etc. In this study, we aim to explore patterns of care-seeking of maternal health services by recently delivered women (RDW) in semi-urban Karachi, Pakistan. Insights of this study will help in identifying and addressing the barriers in care-seeking to minimize delay to improve clinical outcomes. Methods We conducted 32 semi-structured qualitative interviews with RDW with PP sepsis, traditional birth attendants (TBAs), health care providers, and family relatives of RDW to characterize the patterns of care-seeking behaviors, sources of care, and treatment modalities. Community interviews were conducted in Bilal Colony, an urban squatter settlement, and facility interviews were conducted at a high-volume tertiary care facility in Karachi, Pakistan. All interviews were conducted face to face by trained data collectors which were then audio recorded. A codebook was developed manually by reviewing all transcripts and identifying emerging themes. Coded transcripts were entered into NVivo software to develop quotation summaries and models that identified subthemes. Results This study utilized a 3-delay model to determine care utilization in RDW with PP sepsis. Phase 1 indicated limited awareness about PP symptoms, cultural norms, and lack of decision autonomy led to delayed care-seeking, as women depended on male or older female relatives for approval. Two of the most common symptoms of PP sepsis were high-grade fever and foul-smelling discharge, which were deemed as non-severe. Phase 2 findings implied that women initially sought care from TBAs, chemists, and faith healers, or self-medication and tertiary care was their last resort. Financial constraints were also determining care-seeking; Phase 3 indicated that women who sought care at the hospitals were in critical conditions due to prior unskilled care or traditional treatment choices. Conclusion Increasing awareness of PP sepsis and its symptoms via educational programs is essential for not only women but also their family members who play roles in decision-making, Training community health workers and TBAs to recognize signs of PP sepsis and promptly refer women to appropriate facilities could also significantly reduce reliance on inappropriate care sources and ensure timely treatment. Plain language summary Postpartum (PP) sepsis is one of the serious complications after pregnancy resulting from infection of the genital tract occurring at labor or within 42 days of the PP period. Severe cases can lead to organ dysfunction and, ultimately, death. It can also be transferred to newborns, causing early-onset sepsis. PP sepsis is one of the leading causes of death in Pakistan in both hospitals and community settings. These deaths can be prevented by timely care-seeking and treatment. In this study, we explored care-seeking patterns in women who recently delivered in semi-urban Karachi, Pakistan. We conducted semi-structured interviews of recently delivered women (RDW) with PP sepsis, their families, traditional birth attendants, and physicians from the community and a tertiary care hospital. Only physicians were aware of PP sepsis. RDW, their families, and traditional birth attendants were aware of PP complications but couldn’t identify PP sepsis symptoms and were not aware of its severity. One of the major reasons highlighted for the delay in care seeking was that the women were not autonomous in their decisions to visit healthcare facilities and seek care. Husbands and relatives were responsible for decision-making, and their unavailability caused further delay. Trust in services due to previous experience, financial constraints, use of alternate medicine, limited reach, and lack of knowledge were other reasons for not seeking early care. If community healthcare workers are aptly trained to identify early signs of PP sepsis and for timely referral, it can aid in preventing further PP sepsis consequences.